The teaching of homeopathy and its practice in the Brazilian Public Health System (SUS) - Wania Maria Papile Galhardi; Nelson Filice de Barros; Philip Sidney Pacheco Badiz (Faculdade de Medicina de Botucatu (Unesp), 2008)
This study focuses on the formation of the homeopathic physician as one of several actions developed to humanize medical practice. In Brazil, this action occurred outside institutions of higher learning until 2003, when a course specializing in homeopathy was implanted at the Jundiaí Faculty of Medicine (Faculdade de Medicina de Jundiaí, FMJ), with pedagogical practice and attendance for public health service users. The objective of the work was to evaluate the formation of the homeopathic physician at the FMJ and the perceptions of the users, health professionals, professors, course tutors and the faculty council regarding homeopathy and the course. This qualitative study used interviews, the focal group technique and questionnaires. Three analytical categories emerged from the data: a) referential understanding in homeopathy; b) homeopathy as a new paradigm for teaching and attendance within public health; and c) the general course structure. In conclusion, the teaching of homeopathy in university-level institutions with clinical pedagogical practice oriented toward public health is a viable practice.